Digital curling strategy based on game tree search - Yamamoto, M.; Kato, S.; Iizuka, H. (2015 IEEE Conference on Computational Intelligence and Games (CIG), 2015)
Strategy for digital curling based on the game tree search is demonstrated. Digital curling has been developed for simulating curling which is one of the winter sports. We present a curling playing program run on the digital curling simulator. It enable us to decide the direction and the speed of the stone to be delivered for maximizing the evaluation values of resultant game states. The novel evaluation function is constructed and the effective method for reducing the simulation trials is proposed for finding the best shot on the current game state. Our experimental results reveal that our proposed program outperforms the previous rule-based program and competes with the MonteCarlo based program.